PENDIDIKAN FORMAL, KEAHLIAN, PEMBERIAN KOMPENSASI, DAN KINERJA PEGAWAI - Fefianti, Desy; ', Sujianto (Universitas Riau, 2013)
This studyaims to examine and analyze the effect of formal education, skills and compensation partial andsimultaneous effect on employee performance Siak District Secretariat. This study used a surveydesign. The information obtained using a questionnaire or questionnaires, interviews, directobservation or a combination of data gathering techniques that. Results showed no effect levelsand no significant terhdap rectorate if the employee performance and compensation expertise ofemployees in the steady state. Employee expertise and significant effect on the performance of anemployee if the level of education and the provision of compensation in the steady state.Compensation and significant effect on the performance of an employee if the level of educationand skills in a state of permanent employees. This suggests that high compensation levels ofeducation and skills affect employees who have a positive effect on employee performance SiakDistrict Secretariat.